(untitled) (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
Adhesion GPCRs are structurally identified on the basis of a large extracellular region, similar to the Class B GPCR, but which is linked to the 7TM region by a GPCR autoproteolysis-inducing (GAIN) domain [8] containing a GPCR proteolytic site. The N-terminus often shares structural homology with adhesive domains (e.g. cadherins, immunolobulin, lectins) facilitating inter- and matricellular interactions and leading to the term adhesion GPCR [82, 332]. Several receptors have been suggested to function as mechanosensors [254, 234, 315, 32]. The nomenclature of these receptors was revised in 2015 as recommended by NC-IUPHAR and the Adhesion GPCR Consortium [100].